Classroom action research training to develop professional educators for Muhammadiyah school teachers in Belitung - Iful Rahmawati Mega; Haiyudi Haiyudi; Rifki Hanif Setiawan (Community Empowerment, 2024)
Classroom Action Research (CAR) study serves as a crucial indicator for enhancing teacher professionalism. Despite its importance, the competency of teachers in conducting CAR remains relatively low. Various factors contribute to this, including a lack of structured guidance and the burden of administrative tasks. This training program for teachers in Muhammadiyah schools on Belitung Island aimed to improve teachers' professionalism, particularly in understanding and responding to classroom dynamics. The method employed a four-stage training process: planning, preparation, implementation, and evaluation. Following mentoring, the training yielded positive results, with participants successfully developing CAR titles based on their classroom experiences and expressing satisfaction with the acquired knowledge of CAR writing concepts. Furthermore, a portion of the participants expressed a desire for continued training to further enhance their professional capabilities as teachers.